2016
DOI: 10.1155/2016/3050918
|View full text |Cite
|
Sign up to set email alerts
|

Study of Exhaled Nitric Oxide in Subjects with Suspected Obstructive Sleep Apnea: A Pilot Study in Vietnam

Abstract: Background and Objective. The concentration of exhaled nitric oxide (eNO), reflecting the activity of inducible NO synthase in airway epithelium, has been found to increase in patients with obstructive sleep apnea (OSA). This study aimed to measure eNO concentration in patients with suspected OSA and to correlate different eNO parameters with clinical and sleep apnea characteristics. Methods. In this cross-sectional study, all patients underwent in-lab overnight polysomnography (PSG) and eNO measurement using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 21 publications
3
23
0
Order By: Relevance
“…Previous studies using different techniques (electrochemical and chemiluminescence analyzers) have demonstrated elevated NO in the lower airways in obstructive sleep apnea and asthma 2325. The present study showed using electrochemical-based analyzer that the levels of nasal FENO were significantly higher in subjects with AR and AR-asthma than in control subjects, but they were not significantly different between AR and AR-asthma subjects (Table 1).…”
Section: Discussionsupporting
confidence: 47%
“…Previous studies using different techniques (electrochemical and chemiluminescence analyzers) have demonstrated elevated NO in the lower airways in obstructive sleep apnea and asthma 2325. The present study showed using electrochemical-based analyzer that the levels of nasal FENO were significantly higher in subjects with AR and AR-asthma than in control subjects, but they were not significantly different between AR and AR-asthma subjects (Table 1).…”
Section: Discussionsupporting
confidence: 47%
“…Among the included studies, 7 also analyzed the effects of continuous positive airway pressure (CPAP) treatment on airway inflammation: 2 [24,31] evaluated the effects of short-term (2 nights) CPAP therapy while the other 5 [21,22,26,30,33] followed CPAP treatment for more than 1 month. A total of 5 studies [21,24,25,29,31] including 359 subjects were pooled for CANO analysis, and 4 studies [21,24,25,29] with 296 subjects were pooled for J’awNO analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In 5 studies, [16,22,25,28,29] exhaled NO was measured separately before and after overnight PSG to evaluate the variation of FENO levels in the morning and in the evening. For these studies, 2 analyses were performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Technical measurement of exhaled NO was conducted according to manufacturer's instructions, as recommended by the ATS/ERS guideline [6]. The maximal bronchial production rate of NO (J'awNO) and alveolar concentration of NO (CANO) were automatically determined using the two-compartment model and had been reported via Expair's software (Medisoft) as described previously [12,13].…”
Section: Measurement Of Exhaled Nomentioning
confidence: 99%